By the waters of Minnetonka - Dregni, Eric, 1968- (University of Minnesota Press, 2014)
Lake Minnetonka is renowned for its natural beauty as well as the prominent people it has attracted to its shores as a historic site of grand hotels, steamboats and wealthy visitors from around the world, and as the home of the legendary Excelsior Amusement Park. But did you know that early European settlers to the region faced conditions so dire that they named an outlet of the lake "Purgatory Creek"? Or that a ginseng boom brought slaves to Wayzata to harvest the plant's roots? Many know that Frank Lloyd Wright designed famous homes around the lake, but few are aware he was also arrested there for living with his mistress and sent to the Hennepin County jail for "white slavery." By the Waters of Minnetonka uncovers remarkable and hidden facts about the lake and those who have lived on its shores, from the region's original Dakota inhabitants to the present. Nineteenth-century plantation owners made Minnetonka into a summer vacation playground for the wealthy, and Prohibition-era battles led teetotalers to hoax Minneapolis newspapers about bloody clashes between preachers and saloon owners. Eric Dregni, who grew up in Minnetonka, sheds light on intriguing, if at times unsettling, aspects of the lake's history, challenging myths and revisiting elements of the past that have been forgotten or glossed over. He also relates--and sometimes pokes fun at--the opulent, glamorous and sometimes raucous moments that have made Lake Minnetonka an icon of splendid resort living in Minnesota.